بلاغة التعبير في الخطاب القرآني (مجلة إحالات, 2025)
ملخص بلاغة التعبير في الخطاب القرآني لا تدرك إلا بمعرفة لغة القرآن وطرائقه في الأداء البياني. ونزول النص باللسان العربي المبين اقتضى أن تدرك حقيقة الوحي فيه من خلال لغته. ودعي المسلمون من أول فترة من نزوله إلى تدبره باعتباره آخر رسالات السماء إلى الأرض. والمصدر الأول للحقيقة في الإسلام فضل القرآن محط أنظار المسلمين وعنايته يتدارسونه ويتعمقون قضاياه. الكلمات المفتاحية : بلاغة ، تعبير ، الخطاب القرآني ، اللسان العربي ، الأداء البياني . Abstract : The eloquence of the expression of the Quranic discourse can be perceived only by the knowledge of the Quranic language in itself, and by the knowledge of its methods to show a high degree of figurative expressions. The descent of this Quranic text in Arabic indicates that perceiving the sense of the revelation passes through its language. Muslims have been called from the first period of his descendants to contemplate it as the last message from heaven to earth, and as the first source of the truth in Islam. This is why the Quran remains in the sight of the Muslims the centre of the attentions that study it and deeply discuss its issues. Key words: rhetoric, expression, Quranic discourse, Arabic language, figurative expression.